Process evaluation of a pragmatic, multicentre pilot Randomised Controlled Trial (RCT) in primary care: Tailored intervention for COPD and Co-morbidities by Pharmacists and Consultant Physicians (TICC PCP) - Karen Wood; Richard Lowrie; Georgia Smith; David Anderson; Jane Moir; Lynda Attwood; Andrew McPherson; Aziz Sheikh; Elaine Rankine; Frances S. Mair (PLoS ONE, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a growing global challenge. We undertook a process evaluation embedded within the Tailored Intervention at home for patients with moderate-to-severe COPD and Co-Morbidities by Pharmacists and Consultant Physicians (TICC PCP) pilot randomised controlled trial (RCT), which explored patient/stakeholder perceptions of the intervention, acceptability of trial procedures, and barriers/facilitators to intervention implementation. Semi-structured telephone interviews were conducted with intervention patients (20) and stakeholders (10); data were analysed thematically, conceptualised through Normalisation Process Theory. Patient perspectives compared based on socio-economic status (SES). Patients/stakeholders reported positive perceptions of the intervention/trial procedures. Pharmacists provided support across a range of health/social issues. Challenges related to: recruitment; workload/lone-working; managing patient complexity; and data collection. There were suggestions Pharmacists were able to undertake more actions to support patients from low SES areas. Overall, intervention and trial procedures were acceptable to patients and stakeholders. Findings support progression to full-scale RCT.